Respuesta :

z=(kx)/y
3=(k*2)/4
3=k/2
k=6
***
z=6x/y
***
z=6*4/9
z=8/3

Answer:

[tex]z=\frac{63}{4}[/tex]

Step-by-step explanation:

When two variables vary in a directly proportional way, it means that when one variable grows, the other also grows.

This is represented by the following equation

[tex]y = kx[/tex]

Where k is the constant of proportionality

When two variables vary in an inversely proportional way, it means that when one variable grows, the other decreases.

This is represented by the following equation

[tex]y = \frac{k}{x}[/tex]

In this case we know that:

z varies directly with [tex]x^4[/tex] and inversely with y.

We write this as:

[tex]z = k\frac{x ^ 4}{y}[/tex]

We know that When [tex]x = 2[/tex] and [tex]y = 4,\ z = 3[/tex].

So we use this information to find the constant k

[tex]3 = k\frac{2 ^ 4}{4}[/tex]

[tex]3 = k\frac{16}{4}[/tex]

[tex]3 = 4k[/tex]

[tex]k = \frac{3}{4}[/tex]

So the equation is:

[tex]z = \frac{3}{4}\frac{x ^ 4}{y}[/tex]

Finally when x = 4 and y = 9 then:

[tex]z = \frac{3}{4}\frac{4 ^ 4}{9}[/tex]

[tex]z = \frac{3}{4}\frac{4 ^ 4}{9}[/tex]

[tex]z=\frac{63}{4}[/tex]

ACCESS MORE